PENGARUH RETURN ON ASSET DAN RETURN ON EQUITY TERHADAP HARGA SAHAM DI BURSA EFEK INDONESIA - Simanjuntak, Sintauli; Janrosl, Viola Syukrina E (LPPM Universitas Putera Batam, 2020)
Before investing in shares, the company ensures that investments are carried out appropriately using alternative analysis of fundamental or company performance. Return On Assets and Return On Equity is a ratio that shows the company's ability to generate profits by knowing the company's performance. Manufacturing companies have more numbers than other companies, one of which is the food and beverages sub-sector company. This study aims to determine the Return On Asset and Return On Equity variables on stock prices in food and beverages companies listed on the Indonesia Stock Exchange (BEI) in 2014-2018. The population used in this study were 15 companies in the food and beverages sub sector and by using a purposive sampling method a sample of 8 companies was obtained. The technique used for data collection is to use documentation techniques, namely downloading financial report data that has been published from the Indonesia Stock Exchange website. The data collection method uses the method of documentation as well as descriptive statistical tests, classic assumption tests, influence tests and hypothesis tests. The results of this study indicate partially that the Return On Asset variable has no significant effect on stock prices while the Return On Equity variable partially has a significant effect on stock prices. Simultaneously the Return On Asset and Return On Equity variables significantly influence the stock price